Reexamination of the chromium‐51–labeled posttransfusion red blood cell recovery method. Issue 7 (19th April 2019) - Francis, Richard O.; Mahajan, Sonia; Rapido, Francesca; La Carpia, Francesca; Soffing, Mark; Divgi, Chaitanya; Yeh, Randy; Mintz, Akiva; Leslie, Lenhurst; Agrest, Irina; Karafin, Matthew S.; Ginzburg, Yelena; et al.
Abstract : BACKGROUND: The chromium‐51–labeled posttransfusion recovery (PTR) study has been the gold‐standard test for assessing red blood cell (RBC) quality. Despite guiding RBC storage development for decades, it has several potential sources for error. METHODS: Four healthy adult volunteers each donated an autologous, leukoreduced RBC unit, aliquots were radiolabeled with technetium‐99m after 1 and 6 weeks of storage, and then infused. Subjects were imaged by single‐photon‐emission computed tomography immediately and 4 hours after infusion. Additionally, from subjects described in a previously published study, adenosine triphosphate levels in transfusates infused into 52 healthy volunteers randomized to a single autologous, leukoreduced, RBC transfusion after 1, 2, 3, 4, 5, or 6 weeks of storage were correlated with PTR and laboratory parameters of hemolysis. RESULTS: Evidence from one subject imaged after infusion of technetium‐99m–labeled RBCs suggests that, in some individuals, RBCs may be temporarily sequestered in the liver and spleen immediately following transfusion and then subsequently released back into circulation; this could be one source of error leading to PTR results that may not accurately predict the true quantity of RBCs cleared by intra‐ and/or extravascular hemolysis. Indeed, adenosine triphosphate levels in the transfusates correlated more robustly with measures of extravascular hemolysis in vivo (e.g., serum iron, indirect bilirubin, non–transferrin‐bound iron) than with PTR results or measures of intravascular hemolysis (e.g., plasma free hemoglobin). CONCLUSIONS: Sources of measurement error are inherent in the chromium‐51 PTR method. Transfusion of an entire unlabeled RBC unit, followed by quantifying extravascular hemolysis markers, may more accurately measure true posttransfusion RBC recovery.